Makna Simbolik Pertunjukan Kelentangan dalam Upacara Belian Sentiu Suku Dayak Benuaq Desa Tanjung Isuy, Kutai Barat, Kalimantan Timur - Eli Irawati (Jurnal Kajian Seni, 2014)
Kelentangan is a kind of music used in a sequence of Belian Sentiu ceremony, oneof healing rites of Dayak Benuaq Society led by the pemeliatn. The ceremony can beheld when Kelentangan does also come. Kelentangan itself has two meanings, asan instrument or as an ensemble. The performance of Kelentangan in Belian Sentiuceremony is a representation of the myth about belief toward ghosts and the DayakBenuaq ancestor’s spirits. The performance of Kelentangan has a very important rolein the healing procession or also known as ngawat. All of Kelentangan performancesin the Belian Sentiu ceremony are meaningful and contain symbolical meanings in it.They functioned normatively as social adjustment in Dayak Benuaq of Tanjung Isuy,in individual and environmental, and spiritual relationships. The later concerned withghosts and the ancestors’ spirits.